Hired to be daughters: domestic service among ordinary Moroccans - Montgomery, M (2015)
This thesis explores why shaʿbī (roughly, ‘ordinary’) Moroccans so often talk about their domestic workers as daughters, what this means for workers and employers, and how this is changing as community gives way to market. It brings together ethnographic study of urban shaʿbī society, of unmarried rural women who work as domestics, and of the communities from which the latter migrate. Drawing on anthropological discussions of kinship and fosterage, the thesis examines the fading tradition of ‘bringing up’ in which, according to a moral economy, a ‘known’ rural girl could properly be placed in the homes of wealthier Moroccans until marriage. This is giving way to new arrangements in which ‘unknown’ workers are paid a wage and may not stay long, but in which the ethics of charity, religious reward and gratitude still inform expectations from both sides. Geared to play out among neighbours, or at least well-known clients, over a lifetime, these ethics are being disrupted by the easy-come-easy-go of strangers. The thesis contributes to some fundamental concerns of economic anthropology: the atomisation of market exchange, the growing importance of physical marketplaces, and the meanings encoded in a monetary wage versus payment in kind. By putting together perspectives from domestics’ leisure time and life back home, it also questions the relationship between the commodification of labour and individualism. Finally, the thesis discusses a draft law which, if enforced, would mean employing domestics no longer made sense for shaʿbī Moroccans, state intervention respresenting a move away from local forms of empowerment and community. At a broader level, the thesis is concerned with households as internally hierarchical units linked together through exchange to make up society and explores the gendered dimension of household economy in a wider world. This, of course, reaches beyond Morocco, and parallels are suggested with English domestic service.